Philosopher avec des enfants en psychiatrie - Marianne Remacle; Anne François (Recherches en Éducation, 2012)
Since 2002, a workshop of philosophy was established in a child and adolescent psychiatry unit, taking part of the unit treatment program. The procedure of this weekly workshop, which aims to develop specific skills to philosophize (conceptualising, problem seeking and arguing) is governed by a protocol that guarantees the expression of each child and allows the continuation of work by an activity in the visual arts. The use of metaphorical texts supports the process of symbolization and thereby allows children to "dress" their thoughts. Evaluation work, that is set up around the workshop, seeks to understand how this activity is likely to support the work of clinicians and to help children build sense in a way of living that can be very unstructured.